What Happens to Non-Responders in Cardiac Resynchronization Therapy? - Rio, P (2018)
INTRODUCTION AND OBJECTIVES: Left ventricular reverse remodeling (LVRR) is strongly related to the long-term prognosis of patients undergoing cardiac resynchronization therapy (CRT). The aim of this study was to assess the long-term clinical outcome of patients without LVRR at six months after CRT implantation and to determine the prognostic impact of clinical response in this population. METHODS: We analyzed 178 consecutive patients who underwent successful CRT device implantation (age 64±11 years; 69% male; 89% in New York Heart Association [NYHA] functional class III; 35% with ischemic cardiomyopathy). Clinical status and echocardiographic parameters were determined before and six months after CRT implantation. We identified those without criteria for LVRR (≥10% increase in left ventricular ejection fraction with ≥15% reduction in left ventricular end-systolic diameter compared to baseline). Clinical responders were defined by a sustained improvement of at least one NYHA functional class. RESULTS: At six-month assessment after CRT, 109 (61%) patients showed LVRR. During a mean follow-up of 56±21 months, 47 (26%) patients died, with higher mortality in the group without LVRR (36% vs. 20%, p=0.023). Clinical response was greater in patients with LVRR (88% vs. 55%, p<0.001). In patients without LVRR, clinical response to CRT was the strongest independent predictor of survival (hazard ratio: 0.120; 95% confidence interval: 0.039-0.366; p<0.001). CONCLUSION: Although patients without LVRR six months after CRT implantation had a worse prognosis, with higher all-cause mortality, clinical response can be an independent predictor of survival in this population.